ANALISIS PRAKTEK AKAD SEWA KEBUN JERUK DI KABUPATEN BANYUWANGI DALAM PRESPEKTIF MAZDHAB SYAFI’I - Zamroji, Yunus (Jurnal Ekonomi Syariah Darussalam, 2022)
Of the several prevailing systems, the majority used are leases, orange collectors rent oranges from farmers for a certain time, and as long as the rental period is still running and has not been completed, the farmers are not allowed to use their land and the status of the land benefits belongs to the lessee. This research method is a qualitative field research, with the Syafi'i School of jurisprudence and formal juridical approaches, and the data collection method is interviews with people in the Banyuwangi Regency area. The result of the research is that the practice of renting oranges in villages in the Banyuwangi Regency is legal because it is in accordance with the rules set by the Syafi'i School. Actually there is one condition ma'qud 'alaih that is not fulfilled, namely the object of the ijarah transaction is only intended for benefits or services, so it is not permissible to rent out goods in order to obtain benefits in the form of other goods or objects of benefit. However, according to Taqiyyudin As-Subki, at the end of his life, he allowed to rent a tree with the aim of obtaining its fruit.